Magnetoresistance and Fermi Surface of Copper Single Crystals Containing Dislocations - Bian, Qiuping (My University, 2010)
The galvanomagnetic properties and shape of the Fermi surface of copper single crystals containing different density of dislocations have been studied experimentally and theoretically through magnetoresistivity measurement and using effective medium theory respectively.
In experiments, two crystallographic orientations of copper single crystal samples with tensile axis parallel to < 100 > and < 541 > have been plastically strained to various stress levels to introduce different density Nd of dislocations. The experimental data of angle and field-dependent magnetoresistivity measured at temperature T = 2K and in the magnetic filed up to 9 Tesla show that dislocations influence substantially the galvanomagnetic properties of copper crystal samples in the open, extended and closed orbit crystallographic orientations. The results reveal that the pure samples with resistivity ratio RR equal to or larger than 151 show quadratic dependence of transverse magnetoresistivity as a function of the magnetic field in the open-orbit orientation, which changes to linear variation of magnetoresistivity with magnetic fields in highly deformed samples with RR smaller than 138. A quadratic dependence of transverse magnetoresistivity as a function of the magnetic field is significantly suppressed as the density of dislocations increases. The magnetoresistivity decrease with the increase of the density of dislocations was also observed in the closed-orbit crystallographic orientation. Such effect is independent upon the type of dislocations introduced to the crystal lattice.
Measurements of the de Hass-van Alphen effect in plastically deformed copper single crystals have been carried out with torque magnetometer and AC susceptibility options of Quantum Design PPMS-9 system. The oscillation frequencies for the extremal orbits normal to the principal crystallographic directions are obtained through Fourier transform of torque versus inversed field characteristics. By comparing these frequencies with the analogous frequencies obtained for undeformed copper crystals, the changes in the cross-sectional area of the Fermi surface corresponding to the extremal orbits are obtained and the shape of the dislocation-distorted Fermi surface is postulated based on measurements performed.
The effective-medium approximation and Green's function method are applied to model the magnetoresistivity data and to gain insight into the fundamental material properties responsible for the observed magnetoresistivity behavior. The effective magnetoresistivity calculated using a self-consistent method shows a good agreement with the experimental results.
Keywords: magnetoresistance, Fermi, surface, copper, single, crystals, dislocations, field